A framework for mining opinions from user generated content - Amit Kumar Saini (2013)
In this thesis we have presented a scalable framework for mining features and opinions from online reviews. Large scale opinion mining requires scalable components for data storage, along with unsupervised learning solutions for extracting features and opinions, with the ultimate goal of generating meaningful summaries. We have built our system using travel reviews but the system can be used on any domain with minimal changes.